Analisis Pengaruh Kualitas Produk Harga Dan Promosi Terhadap Keputusan Pembelian Pada Produk Kecantikan Wardah - Cheren Adina Putri (CV. Aksara Global Akademia, 2023)
This study aims to prove partially and simultaneously the effect of product quality, price, and promotion on purchasing decisions for wardah beauty products. This research is a quantitative descriptive survey. The sampling technique that has been used is the leddy formula and consists of 50 respondents. The results of this study are that product quality has a significant effect on purchasing decisions for wardah beauty products, price has a significant effect on purchasing decisions for wardah beauty products, and advertising has a significant effect on purchasing decisions for wardah cosmetic products. Wardah beauty products have very good quality products, prices and advertising promotions so that they have a significant influence on purchasing decisions for wardah beauty products.